Beyond the Nordic Welfare State: Extending Social Investments with Interventions - Erola, Jani; Moisio, Pasi; Peltoniemi, Johanna (Edward Elgar Publishing, 2026)
This timely book showcases a new approach to social investment which links investments to evidence-based interventions and clear effectiveness criteria, enhancing the efficiency, equitability, and sustainability of welfare policies.